THE USE OF CODE-SWITCHING BY EARLY YEAR STUDENTS IN VIRTUAL CLASSROOM - Zenitha, Ni Putu Ria (Lingua Scientia, 2021)
AbstractThis paper reports the types of code-switching patterns used by students of early years in one of international schools in Bali while they had online classes. The research design used in this study was a qualitative case study. By following the purposive random sampling, ten students were selected as the research participants. They were coming from a mixed-marriage family. The data were collected through observation and in-depth interview. The data were analyzed by implementing two layers of data analysis: Interactive qualitative analysis of Miles, Huberman, and Saldana (2014) and categorization of Muysken’s code-switching theory (2000). The results show that there were insertion and alternation types of code-switching, which were used by students during local subject classes specifically Bahasa Indonesia and Indonesia culture in early years and occurred in the forms of simple sentences with common words as their replies of teachers’ instructions. It was followed by the reasons of teachers to get them used to Bahasa Indonesia and introduce them Indonesia cultures, and other good values related to attitudes and manners as well. Thus, it could encourage them to be aware regarding country language used where they live at the moment. This research was expected to give pedagogical implications for early years’ teachers and parents in understanding the importance of bilingualism for students’ language development and cultural cross-understanding. Keywords: Code-Switching Pattern, Bilingualism, Local Subjects, Early Years